FACTORS INFLUENCING PUBLIC BEHAVIOUR TO IMPROVE POSYANDU VISIT KENAGARIAN SIMPANG DISTRICT OF SIMPANG ALAHANMATI PASAMAN - SRI HARTATI, LUSI; Juita, S.Pd. M.Si, Erna; Prari Keslan, Widya (Pendidikan Geografi, 2014)
ABSTRAKThis research aim to determine the factors that influence peoples behavior in improving the neighborhood health center visits Simpang village Simpang Alahanmati district Pasaman region.This research is a descriptive correlational. Population in this study were all mothers who did not attend to the Posyandu at Simpang village Simpang Alahanmati district Pasaman region are 380 mothers, samples were taken with a proportional random sampling technique and proportion 15% with a sample of 59 mothers.The results of the study found that : (1) There is a degree of influence on the behavior of public education in improving the neighborhood health center visits in Simpang village Simpang Alahanmati District Pasaman region because tcount > t table (3,881 > 2,00), the strength of the relationship was (r = 0,457) and the contribution of small (20,9%), (2) There is no effect on the income level of peoples behavior in increasing posyandu in Simpang village Simpang Alahanmati District Pasaman region because of tcount < t table ( 0,595 < 2,00), the effect is very low (r = 0,079) and a very small contribution (0, 6%), (3) There is no effect on the behavior of public accessibility in improving the neighborhood health center visits in Simpang village Simpang Alahanmati District Pasaman region because of tcount < t table (-0,427 < 2,00), the magnitude of the effect is very low (r = 0,056) and a very small contribution (0,3%) and (4) There is the influence of education level, income level and accessibility together to improve peoples behavior in a visit to a neighborhood health center in Simpang village Simpang Alahanmati District Pasaman region because of F count > F table (4,942 > 2,78), all three variables influence the behavior of people in increasing posyandu in Simpang village Simpang Alahanmati District Pasaman region including medium category (r = 0,461) and included a small contribution (21,2%).